2022
DOI: 10.3390/vetsci9100572
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Case Series of Clinical Signs and Adrenocorticotrophin (ACTH) Concentrations in Seven Horses Transitioning to Pituitary Pars Intermedia Dysfunction (PPID)

Abstract: Poor recognition of subtle clinical abnormalities and equivocal ACTH concentrations make early diagnosis of PPID difficult. Progressive clinical findings and corresponding ACTH concentrations in horses transitioning to PPID over time have not been documented. Seven horses with ACTH concentrations equivocal for PPID (utilizing locally derived, seasonally adjusted diagnostic-cut off values (DCOV)) and no clinical signs of PPID were selected. Sequential measurement of basal and thyrotropin-releasing hormone (TRH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Both tests should be interpreted in accordance with appropriate DCOV, RI or seasonal thresholds, depending on the clinical presentation and need to reduce false negative or false positive results. Diagnosis based on clinical signs alone is possible, though once clinical signs are obvious, the disease could be severe [ 113 ]. To increase quality of life and athletic performance, treatment with pergolide mesylate is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both tests should be interpreted in accordance with appropriate DCOV, RI or seasonal thresholds, depending on the clinical presentation and need to reduce false negative or false positive results. Diagnosis based on clinical signs alone is possible, though once clinical signs are obvious, the disease could be severe [ 113 ]. To increase quality of life and athletic performance, treatment with pergolide mesylate is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…However, the disease can have severe, life threatening consequences and ability to diagnose subclinical or mild PPID and initiate treatment before end-stage disease may be beneficial [ 40 , 47 , 113 ]. A recent prospective case series measured basal and TRH-stimulated ACTH concentrations in seven horses with subclinical PPID, and found that TRH-stimulation testing in late summer or early autumn (February and March in Australia) identified most horses that transitioned to clinical PPID over a 3.5 year period [ 113 ]. This was a small case series, so further research is required to determine if early diagnosis is warranted.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…One systematic review 17 and 13 additional publications [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] were identified that provided data on the frequency of clinical signs within veterinary-diagnosed PPID cases, which were considered in combination with the outcomes from the panel Delphi consultation to categorise clinical signs by the index of clinical suspicion (Table 5). Generalised or regional hypertrichosis (± delayed/abnormal coat shedding) was the most commonly reported sign across all studies (Figures 1-5).…”
Section: Case Selection For Diagnostic Testing and Pretest Probabilitymentioning
confidence: 99%